Resolusi Konflik Pencegahan Disintegrasi Bangsa Melalui Legalitas Hukum Syariat di Aceh - Muhammad Sholeh; Nur Rohim Yunus; Ida Susilowati (SALAM: Jurnal Sosial dan Budaya Syar-i, 2016)
Abstract:Efforts that have been made by the government of the Republic of Indonesia to reduce conflict in Aceh in the form of various policies. From the pattern of violence, mediation, enactment of the Regional Military Operation, to finally negotiations for peace. Negotiations eventually served as the final conflict resolution in order to quell the raging turmoil. After the Aceh Tsunami in December 2004, an agreement was finally reached in Helsinki between the government of the Republic of Indonesia and the elders of the Free Aceh Movement. Among the resolutions obtained are the enactment of Sharia law or Qonun in Aceh, as a legal law that regulates the life of the Acehnese in an Islamic manner.Keywords: Conflict Resolution, Sharia Law, National Disintegration Abstrak: Upaya yang telah dilakukan pemerintah Republik Indonesia dalam meredam konflik di Aceh dalam bentuk kebijakan beranekaragam. Dari pola kekerasaan, mediasi, pemberlakuan Daerah Operasi Militer, hingga perundingan untuk perdamaian. Perundingan akhirnya dijadikan sebagai resolusi konflik terakhir guna meredam gejolak yang berkecamuk. Pasca terjadinya Tsunami Aceh pada bulan Desember 2004, akhirnya dibuatkan kesepakatan di Helsinki antar pemerintah Republik Indonesia dan para tetua Gerakan Aceh Merdeka. Diantara resolusi yang didapatkan adalah pemberlakukan hukum Syariah atau Qonun di Aceh, sebagai hukum legal yang mengatur kehidupan masyarakat Aceh secara Islami. Kata Kunci: Resolusi Konflik, Hukum Syariah, Disintegrasi Bangsa